LINGUOCULTURAL ASPECTS OF GENDER LEXICON (Scientific journal of the Fergana State University, 2025)
This article mainly covers the expression of cultural characters in fiction through lexical units with gender characteristics, the activation of male and female relationships in the linguistic space with gender lexicon, as well as practical analysis of the use of lexemes in mutual appeals of husband and wife in the family in Uzbek and English fiction.  It is also stated that the prover, which is a sign of folk culture, as well as the role of gender lexical units in the linguistic activation of idioms are considered.